The Influence of Social Media Use on the Performance of Employees at the Samarinda City Transportation Agency - Nur, Sri Wahyu Mening Tyas; Sary, Kezia Arum; Dwivayani, Kadek Dristiana; Alfando W.S, Johantan (Riwayat: Educational Journal of History and Humanities, 2025)
In the era of globalization and technological advancement, government agencies are required to adopt the Internet and social media to improve service quality and develop human resource performance. Social media plays a crucial role in facilitating communication and collaboration in the workplace, enabling the rapid and efficient exchange of information and knowledge. This helps improve human resource performance in achieving the goals set by government agencies, aligning with the expectations and targets established. To determine the influence of social media use on the performance of employees at the Transportation Department of Samarinda City. This study employs a descriptive, quantitative approach, drawing on the uses and gratification theory. The sampling technique employed purposive sampling, resulting in 100 respondents. The results of this study indicate that the use of social media has a significant influence of 77.4% on employee performance. In comparison, the remaining 22.6% is influenced by other factors not examined in this study, which means that the hypothesis that social media use has a positive and significant effect on employee performance is supported.